Satisfying the Need for Relatedness Among Teachers: Benefits of Searching for Social Support - Maas, Jasper; Schoch, Simone; Scholz, Urte; Rackow, Pamela; Schüler, Julia; Wegner, Mirko; Keller, Roger (Frontiers in Education, 2022)
The satisfaction of teachers’ need for relatedness is an important precondition for teachers’ well-being. Receiving social support plays an important role in satisfying the need for relatedness. Following job crafting theory, the present study aims to examine (1) whether searching for social support results in an increase in the satisfaction of the need for relatedness and (2) whether this effect is mediated by an increase of received social support from the school principal and from colleagues. Using longitudinal data (N = 1071) we calculated residualized change scores and applied structural equation modelling to test the hypothesized mediation model. Results confirmed the beneficial effect of searching for social support on the satisfaction of the need for relatedness. This effect included a direct effect and an indirect effect through the receipt of social support from colleagues. The receipt of social support from the school principal was positively related to searching for social support but was unrelated to the satisfaction of the need for relatedness. These findings emphasize the possibility that teachers have in building up strong and supportive relationships within school teams and thereby contributing to better well-being among teachers.